PEMANFAATAN MEDIA ONLINE BERITAJAKARTA.ID DALAM PUBLIKASI PROGRAM KERJA PEMPROV DKI JAKARTA - Yumna Aisyah; Rani Chandra Oktaviani (Avant Garde, 2018)
As of right now, the current expanding mass media is digital media, which makes it easier for information to be obtained by people all over the world. The development of the digital media has broazught changes to one of the tasks of government public relations including the publication or dissemination of information. Public Relations of DKI Jakarta Provincial Government utilizes BeritaJakarta.com online media for the publication of Jakarta Provincial Government's work program. This study aims to find out how the utilization of beritajakarta.id online media in publishing the work program of the DKI Jakarta provincial government and to find out whether the advantages and disadvantages of the DKI Jakarta provincial government are using beritajakarta.id.The theory of Computer Mediated Communication together with qualitative data collection method with a semi-structured interview are used in this thesis. The result shows that beritajakarta.id is used by Pemprov DKI Jakarta to notify the outcome of their meetings and to report their overall work programs, starting from the planning phase through to the completion. Furthermore, Pemprov DKI Jakarta also utilizes beritajakarta.id to announce their new policies. The conclusion obtained is that the Provincial Government uses beritajakarta.id as a function of GPR in the process of information dissemination and policy